CURRENT STATE OF RADIOLOGICAL DIAGNOSTICS OF PATIENTS WITH ACUTE CEREBRAL DISEASE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Hemorrhagic stroke is a spontaneous (non-traumatic) hemorrhage into the cranial cavity. The term "hemorrhagic stroke" is usually used to refer to intracerebral hemorrhage that occurs as a result of any vascular disease of the brain: atherosclerosis, hypertension, and amyloid angiopathy. Most often, hemorrhagic stroke occurs against the background of high blood pressure